Quantitative fine-structural analysis of olfactory cortical synapses - Schikorski, T. (The National Academy of Sciences, 1999)
To determine the extent to which hippocampal synapses are typical of those found in other cortical regions, we have carried out a quantitative analysis of olfactory cortical excitatory synapses, reconstructed from serial electron micrograph sections of mouse brain, and have compared these new observations with previously obtained data from hippocampus. Both superficial and deep layer I olfactory cortical synapses were studied. Although individual synapses in each of the areas—CA1 hippocampus, olfactory cortical layer Ia, olfactory cortical area Ib—might plausibly have been found in any of the other areas, the average characteristics of the three synapse populations are distinct. Olfactory cortical synapses in both layers are, on average, about 2.5 times larger than their hippocampal counterparts. The layer Ia olfactory cortical synapses have fewer synaptic vesicles than do the layer Ib synapses, but the absolute number of vesicles docked to the active zone in the layer Ia olfactory cortical synapses is about equal to the docked vesicle number in the smaller hippocampal synapses. As would be predicted from studies on hippocampus that relate paired-pulse facilitation to the number of docked vesicles, the synapses in layer 1a exhibit facilitation, whereas the ones in layer 1b do not. Although hippocampal synapses provide as a good model system for central synapses in general, we conclude that significant differences in the average structure of synapses from one cortical region to another exist, and this means that generalizations based on a single synapse type must be made with caution.